"Rapiéçages faits avec sa propre étoffe": Discontinuity and convergence in Romance prefixation. (July 2019) - Iacobini, Claudio
Abstract : This article provides a comprehensive overview of prefixation in Romance languages putting in relation the differences between standard and non-standard varieties in the current synchronic stage and, from a diachronic perspective, the different productivity of verbal prefixation and nominal and adjectival prefixation over the history of Romance languages. The article also deals with the relations between system-internal factors, such as the delimitation and interaction between native and foreign word-formation, as well as the competition between verbal prefixation and other linguistic resources through which spatial information can be expressed. The focus will also be placed on system-external factors, including the diffusion in common language of learned terms which have contributed to revitalizing nominal and adjectival prefixation, although not verbal prefixation. Such an approach makes it possible to account for the higher productivity in current standard Romance languages of nominal and adjectival prefixation compared with verbal prefixation. Furthermore, it provides an explanation for the differences between standard and non-standard Romance languages with regard to the productivity of nominal and adjectival prefixation. The replacement of spatial verbal prefixes with verbs expressing path in the root is interpreted as the result of a more general restructuring of space encoding.